Immune checkpoint inhibitor-induced thyroiditis and its potential mechanisms - Mao, Xueqian; Mao, Chaoming; Liu, Jiameng; Wang, Xi; Mao, Yufei (Frontiers in Endocrinology, 2025)
The expanding clinical utilization of immune checkpoint inhibitors (ICIs) in oncology has brought increasing attention to thyroid dysfunction as a prominent immune-related adverse event (irAE). Elucidating the pathophysiological mechanisms underlying ICI-induced thyroiditis represents a critical step toward developing evidence-based diagnostic protocols and targeted therapeutic interventions for cancer patients undergoing immunotherapy. This comprehensive review systematically examines current advances in understanding the etiopathogenesis of ICI-induced thyroiditis. First, we described pharmacological characterization of ICIs, then discussed multifactorial analysis of cellular and molecular contributors to thyroid autoimmunity following ICI administration and finally analyzed critical evaluation of emerging hypotheses regarding primary pathogenic drivers. Through this review, we aim to establish mechanistic connections between ICI pharmacodynamics and thyroid tissue immunopathology.